2018
DOI: 10.3389/fmicb.2018.02032
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Prophage-Free Derivative Strain of Lactococcus lactis ssp. lactis IL1403 Reveals the Importance of Prophages for Phenotypic Plasticity of the Host

Abstract: Lactococcus lactis is a lactic acid bacterium of major importance for the dairy industry and for human health. Recent sequencing surveys of this species have provided evidence that all lactococcal genomes contain prophages and prophage-like elements. The prophage-related sequences encompass up to 10% of the bacterial chromosomes and thus contribute significantly to the genetic diversity of lactococci. However, the impact of these resident prophages on the physiology of L. lactis is presently unknown. The genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 69 publications
2
30
0
Order By: Relevance
“…However, it is well-known that prophages can switch to the lytic life cycle, in which the prophage DNA is excised from the host genome. Although such process often accompanied by lysis of the host cells, curing of prophages from host bacteria was reported in some bacteria (Euler et al, 2016;Aucouturier et al, 2018). Therefore, it is necessary to ensure there is no spontaneous release of prophage before using a lysogenized bacterium as a live attenuated vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is well-known that prophages can switch to the lytic life cycle, in which the prophage DNA is excised from the host genome. Although such process often accompanied by lysis of the host cells, curing of prophages from host bacteria was reported in some bacteria (Euler et al, 2016;Aucouturier et al, 2018). Therefore, it is necessary to ensure there is no spontaneous release of prophage before using a lysogenized bacterium as a live attenuated vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Phages E1, and p6/4 exhibited poor lysis (turbid, small plaques, low titer compared to their reference strains) of the IL1403 strain, while the cremoris type strains (MG1363 and NZ9000) were fully resistant to these phages. Recently, it has been shown that resident prophages may influence host susceptibility and the phage plaquing efficiency [60]. This effect may be due to a yet undermined prophage-encoded anti-Ceduovirus defense mechanism, similar to the described super-infection exclusion (Sie) phenomenon against Skunavirus phages.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, antimicrobial susceptibility was observed in general to be higher in the presence of resident prophages than in prophage-cured derivatives [9]. In the present study, a complementary approach was taken whereby lysogens were generated and evaluated for antimicrobial susceptibility where newly acquired prophages have been integrated in the host chromosome.…”
Section: Lysogen-specific Impacts Of Antimicrobial Compoundsmentioning
confidence: 96%
“…The susceptibility of L. lactis 3107 and its lysogenized derivatives 3107-TPlys, -Dublys, and -LC3lys to antimicrobials was determined using the method described by Aucouturier et al (2018). Briefly, overnight cultures of 3107 and its derivative strains were diluted 10-fold in Ringer's solution (Sigma, St. Louis, MO, USA).…”
Section: Lysozyme and Nsin Susceptibility Assaysmentioning
confidence: 99%
See 1 more Smart Citation